Prevalence of Class I Caries Among Out Patients with Diabetes Visiting A Private Dental Hospital - A Retrospective Analysis - B, REVATHI.; SANDHYA, RAGHU; KUMAR, KIRAN (The journal of contemporary issues in business and government, 2021)
Diabetes is a metabolic disorder that is common among all ages of people worldwide. Whereas Dental caries is one of the most prevalent and preventable diseases. Both diabetes and caries are associated with carbohydrate intake.Diabetic patients have increased sucrose level and less amount of fluoride content that promotes demineralisation thereby providing the favourable environment for caries progression.However there is still some controversy regarding the relationship between diabetes and caries. Hence the aim of the present study was to assess the prevalence of class 1 dental caries in patients with type 2 diabetes mellitus. We reviewed patient records and analysed the data of 86000 patients between June 2019 and march 2020 from which 600 diabetic patients were included in the study and assessed for age,gender and presence of class 1 caries in each tooth. Collected data was tabulated in excel sheet and imported in SPSS version 17 for statistical analysis. Among 600 diabetic patients, 55.9% showed presence of caries and 44% were without class 1 caries. The result was highly significant (t-test; P<0.001). 40 to 50 years age group patients showed high prevalence of caries(64%) and 20 to 30 age groups showed minimal prevalence(17.6%). Males showed higher prevalence than females with 56.4% and 43.5%. This result was not significant (Chi-square test; P=0.013). Tooth number 37(15.5%) showed high incidence followed by 38(7.1%) and 47(6.8%). Mandibular posteriors(60.3%) showed higher prevalence than maxillary posteriors (30.3%).